Penerapan Representational State Transfer (REST) Pada Push Notification Whatsapp Untuk Layanan Informasi Akademik - Anggra Triawan; Wisnu Alipudin (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Higher education is an educational institution within the national education system in all countries. Its position is not much different from primary or secondary education, which functions to develop the potential of students to grow and develop as normal members of society, but universities have a mission that goes beyond just providing graduates who are smart, reliable in their knowledge organization and able to apply in the world of work. . Higher education must be able to deliver students to understand themselves, determine their role in society and as human beings who are much better than before. Push notifications, a service that is widely used for notifications via short messages on smartphones. With the Push Notification service, users can be helped in terms of brief notifications. In its implementation, Push Notification can be used in various daily needs, for example to monitor attendance, update the latest news, and so on, by combining whatsapp and academic push notifications will result in a search for values very easily when using the WhatsApp application.